2013
DOI: 10.1186/1471-2474-14-61
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic thoracic spine fracture in presence of Parkinson’s disease and diffuse ankylosis: successful management of a challenging condition

Abstract: BackgroundPatients with Parkinson’s disease have higher risk of complications and revision surgery following spine surgery. Spinal fracture in an ankylosed spine is also difficult to treat. We recently treated a case of thoracic spine fracture in a patient with Parkinson’s disease complicating a severely ankylosed spine. There is no report describing surgical treatment of spine fracture in such a difficult condition, thus, we firstly report the case and discuss the reasons for a successful result.Case presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…PD is a degenerative neurological disease associated with loss of self‐sufficiency and is characterized by its cardinal features of tremors, rigidity, bradykinesia, and postural instability 16 . Osteoporosis is a “hidden nonmotor face” of PD and a cause of considerable morbidity in the older general population, patients with PD usually have poor bone quality 17,18 . Invernizzi et al 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD is a degenerative neurological disease associated with loss of self‐sufficiency and is characterized by its cardinal features of tremors, rigidity, bradykinesia, and postural instability 16 . Osteoporosis is a “hidden nonmotor face” of PD and a cause of considerable morbidity in the older general population, patients with PD usually have poor bone quality 17,18 . Invernizzi et al 19 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Osteoporosis is a "hidden nonmotor face" of PD and a cause of considerable morbidity in the older general population, patients with PD usually have poor bone quality. 17,18 Invernizzi et al 19 suggested that osteoporosis is very common in patients with PD, affecting up to 91% of women and 61% of men. Compared with healthy people, the normal activities of PD patients were significantly reduced.…”
Section: Case Presentationmentioning
confidence: 99%